Teachers' capital and relations with parents: A comparison between Israeli Jewish and Arab teachers. (November 2016) - Addi-Raccah, Audrey; Grinshtain, Yael
Abstract: Under neo-liberal policies, parents gain influence in schools. Following Bourdieu's notion of field, we examined teachers' views toward parents and their possession of feminine, social, and cultural capital in Jewish and Arab schools in Israel. Teachers (n = 959) from 51 randomly selected schools filled out a questionnaire. Findings revealed that Jewish and Arab teachers maintain differing relations with parents that include disengagement, threat and collaboration. Jewish teachers' perceptions of parents relate to their possession of divers types of capital, whereas Arab teachers count on their social capital. The findings fit the dimensions of individualism-collectivism and teachers' social position. Highlights: Teachers simultaneously have collaborative and conflicting relations with parents. Jewish and Arab teachers cultivate different relations with parents. Different teachers' capitals are related to different relations with parents. In their relations with parents Arab teachers count on their social capital. Jewish count on their social, cultural and feminine capitals.